Peranan Sistem Informasi Akuntansi sebagai Alat Bantu Manajemen dalam Pengambilan Keputusan Anggaran Biaya pada Perusahaan Daerah Air Minum (PDAM) Kota Makassar - Faidul Adzim (-)
This research was conducted using qualitative descriptive analysis method. This method is done by making a picture or painting in a systematic, factual and accurate information on the facts, characteristics, and relationships between phenomena vitality. Pengumpulan data is done with interviews and collecting data facts in the data processing procedures of accounting information as well as connect with data existing theoretical. As well as the company's data in the form of a general overview of the company.The results of the study concluded that the accounting information system can function effectively and efficiently in helping management determine the budget. data processing accounting information in accordance with the accounting procedures has been established to produce financial reports in a timely, reliable and relevant so that it can be a benchmark in the preparation of the budget.